ORGANIZING ACTIVITIES FOR CHILDREN IN THE ORIENTATION OF STEAM EDUCATION - et. al., Nguyen Thi Ut Sau, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The content of the article analyzes the advantages of STEAM education in the implementation of the kindergarten program in the current period and introduces the plan and results of activities for preschool children according to the STEAM orientation at the school at “May 19” Kindergarten - Thai Nguyen City - Thai Nguyen Province. On the basis of theoretical analysis and current situation, the author proposes a number of recommendations to effectively organize activities for preschool children according to the STEAM orientation in Preschools.